The Honorable Miracle of the Ummah of Muhammad - may God bless him and grant him peace - in the Sunnah of the Prophet (ascites as an example) (مجلة جامعة سرت للعلوم الانسانية, 2023)
The universe with its systems and estimation is from God's creation, and man - obedient and disobedient - is created for God, and God's balance is between justice and grace, and God's grace requires that the systems of what He was created be violated for the sake of those He created in honor of Him, just as God's justice requires that the systems of what He be violated be a denial and an insult to those who created, and for what We learned that God’s love necessitates the one who is compelled to break these laws for the sake of the one he loves, so by knowing these constants, we realize that one of the greatest honors is, What God honored the ummah of our Prophet Muhammad - may God bless him and grant him peace - and it is what was mentioned in the purified Sunnah of the Prophet in the issue of asking for water in the event of a drought (ascites), and what is in it of a miracle that includes dignity, and support for those who love, and perhaps what preoccupies me as a researcher is The miraculous aspect between dropsy and precipitation; That relationship that stems from support and victory, that relationship that, if the scales of the mind are judged in it, stops at a station that the mind cannot overcome; This is because the mind is in the highest degree of its surroundings unable to perceive it, so by contemplating this worship that meets the conditions achieved for the results, it is achieved with certainty that: (the miraculous).
Keywords: honorary miracle; the face of miracle; dropsy